Another modernity: Elia Benamozegh's Jewish universalism - Boulouque, Clémence (Stanford studies in Jewish history and culture, 2020)
Introduction -- Benamozegh's texts and contexts : Morocco, the Risorgimento, and the disputed manuscript -- Universalism as an index of Jewish modernity -- Beyond binaries : Kabbalah as a tool for modernity -- Past enmity : modes of interreligious engagement and Jewish self-affirmation -- Epilogue.